2001
DOI: 10.1021/jp0128527
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Resonance Raman Study of the Reaction of Isodiiodomethane with Cyclohexene:  Implications for the Mechanism of Photocyclopropanation of Olefins Using Ultraviolet Photolysis of Diiodomethane

Abstract: We examine the chemical reaction of isodiiodomethane (CH 2 I-I) with cyclohexene using time-resolved resonance Raman spectroscopy. Our results indicate that CH 2 I-I reacts with cyclohexene to produce an iodine molecule leaving group on the 5-10 ns time scale which then almost immediately forms a I 2 :cyclohexene complex. This in conjunction with previous results from photochemistry experiments and recent density functional theory calculations indicates that isodiiodomethane is the methylene transfer agent mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 41 publications
5
69
0
Order By: Relevance
“…It is interesting that the decay of CH 2 I-I in methanol (kϭ1.3ϫ10 8 s Ϫ1 ) is similar to that for 25%-50% water in acetonitrile solvent that had measured time constant of 4640-1860 ps and corresponding rate constants of kϭ2.2 The hypothesis that CH 2 I-I reacts with the O-H bonds of water and alcohols is consistent with the carbenoid behavior of isodiiodomethane (CH 2 I-I) and other isopolyhalomethanes as shown towards carbon double bonds to make cyclopropanated products. 87,89,[93][94][95]97 The chemical reactivity of CH 2 I-I is similar to that of singlet methylene towards CvC bonds in making cyclopropanated products with high stereospecificity and little C-H-insertion products. 93,99,100 Carbenes and carbenoids like singlet methylene 101-104,106 -108 and dichlorocarbene (:CCl 2 ) 109,110 can react with O-H bonds of water to produce CH 3 OH and CHCl 2 OH products and can also react with O-H bonds in alcohols.…”
Section: B Picosecond Time-resolved Resonance Raman Experimentsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is interesting that the decay of CH 2 I-I in methanol (kϭ1.3ϫ10 8 s Ϫ1 ) is similar to that for 25%-50% water in acetonitrile solvent that had measured time constant of 4640-1860 ps and corresponding rate constants of kϭ2.2 The hypothesis that CH 2 I-I reacts with the O-H bonds of water and alcohols is consistent with the carbenoid behavior of isodiiodomethane (CH 2 I-I) and other isopolyhalomethanes as shown towards carbon double bonds to make cyclopropanated products. 87,89,[93][94][95]97 The chemical reactivity of CH 2 I-I is similar to that of singlet methylene towards CvC bonds in making cyclopropanated products with high stereospecificity and little C-H-insertion products. 93,99,100 Carbenes and carbenoids like singlet methylene 101-104,106 -108 and dichlorocarbene (:CCl 2 ) 109,110 can react with O-H bonds of water to produce CH 3 OH and CHCl 2 OH products and can also react with O-H bonds in alcohols.…”
Section: B Picosecond Time-resolved Resonance Raman Experimentsmentioning
confidence: 99%
“…73,74,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92] We explored the chemical reactivity of isopolyhalomethanes towards olefins theoretically and experimentally. 87,89,[93][94][95][96][97][98] Density functional theory ͑DFT͒ calculations revealed that the CH 2 I-I species can readily react with ethylene to produce a cyclopropane product and I 2 leaving group with a barrier of only 2.9 kcal/mol, but the CH 2 I radical and CH 2 I ϩ cations have much more difficult pathways to make cyclopropanated products. 93,94 TR 3 experiments showed that CH 2 I-I reacts with cyclohexene on the 5-10-ns time scale to make an I 2 leaving group that immediately complexes with the solvent to make an I 2 :cyclohexene complex 95 under conditions similar to those that observed significant formation of the cyclopropanated product of cyclohexene ͑norcarane͒ after ultraviolet photolysis of CH 2 I 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These experimental and theoretical results indicate that CH 2 I-I is the main methylene transfer agent for the cyclopropanation reactions of olefins employing ultraviolet photoexcitation of diiodomethane and a reaction mechanism was proposed. [65][66][67] Because the CH 2 I-I species has only one atom less than the classical Simmons-Smith carbenoid (IZnCH 2 I), the CH 2 I-I species is an interesting model system for Simmons-Smith type carbenoids.…”
Section: Introductionmentioning
confidence: 99%